2014
DOI: 10.15835/nbha4229671
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Propagation of Sweet and Sour Cherry Rootstocks

Abstract: The paper presents a protocol for micropropagation of Prunus sp. rootstocks included in the sweet and sour cherry breeding program. Germplasm diversity for rootstock breeding derives from natural populations, where conditions and biological vectors for systematic infection with viral diseases are constantly present. The establishment of aseptic culture depends primarily on the explant type, as all selections were collected from natural habitat. For nearly all investigated selections, dormant buds were the favo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Gisela 5 low-vigorous cherry rootstock is mainly propagated by micropropagation throughout the year (Ružić and Cerović, 2002;Ružić and Cerović, 2003). Bošnjaković et al (2013) and Dorić et al (2014) reported successful micropropagation when dormant buds, rather than actively growing shoot tips, were used as an explant source in P. fruticosa Pall. and P. mahaleb L., regardless of genotype diversity.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Gisela 5 low-vigorous cherry rootstock is mainly propagated by micropropagation throughout the year (Ružić and Cerović, 2002;Ružić and Cerović, 2003). Bošnjaković et al (2013) and Dorić et al (2014) reported successful micropropagation when dormant buds, rather than actively growing shoot tips, were used as an explant source in P. fruticosa Pall. and P. mahaleb L., regardless of genotype diversity.…”
Section: Resultsmentioning
confidence: 99%
“…To break dormancy, Druart (2013) recommended cold storage of twigs for 1 month at 2 °C. In P. fruticosa and P. mahaleb, dormancy did not adversely affect culture initiation, multiplication, shoot elongation, or rooting (Bošnjaković et al, 2013;Dorić et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ability of explants to regenerate depends on the initiation period. As a rule, explants selected during the period of active growth of shoots have the highest regenerative activity [10].…”
Section: Introductionmentioning
confidence: 99%
“…One of the factors for the success of reproduction is the composition of the nutrient medium. Most often, for clonal micropropagation of rootstocks of small-seed cultures (cherries, sweet cherries), modified media of Murashige and Skoog (MS), DKW, WPM, Schenk and Hildebrandt (SH) are used, with various variations of hormonal substances, vitamins, macronutrients, sucrose [10][11][12][13][14][15] , for large-seed crops (plum, cherry-plum, apricot, peach) -the environment of Murashige and Skoog (MS), DKW, Quorina-Lepuavra (QL) [4,[16][17][18][19]. Optimizing the composition of the environment for a specific plant genotype is of particular importance, because even within the same species, plants may exhibit different reactions.…”
Section: Introductionmentioning
confidence: 99%